Economic Cost of Road Traffic Accidents in Twin Cities, Pakistan - Komal Chaudhry; Muhammad Jawed Iqbal (European Scientific Journal, ESJ, 2018)
Road Traffic Accidents in developing countries are a serious concern in terms of safety and economy. RTAs share a considerable amount of overall life, resource, and productivity losses. It has become essential to monetize RTAs to aid the policymakers, economists, and the state government to efficiently select the cost-effective countermeasure for the safety of road users. The costs can be utilized in framing cost-effective safety measures and policies. This paper focuses on estimating the overall costs of Road Traffic Accidents in the city of Rawalpindi/Islamabad, Pakistan, by using the Human Capital Approach to estimate the monetary amount that the Road Traffic Accidents have cost to the cities in the year 2016. The research has categorized the costs into 5 main components, namely: medical costs, property damage costs, loss output, human loss, and administrative costs. A total of 10187 incidents have been recorded in the cities involving 12573 victims and 18136 vehicles. Results suggested that a total of pkr 2.183 billion has been incurred by the State of Pakistan with a loss of about 0.0074% to the GDP. The breakdown of the costs was as follows: Medical costs (pkr 93,898,640), and it comprises 4.26% of the total cost; Property damage costs include vehicular and property damage repair (pkr 214,840,463), and it comprises 9.84% of the total cost; Loss output (pkr 1,316,000,000), and it comprises 60.27% of the total cost; Human costs (pkr 473,584,345), and it comprise 21.69% of the total cost; Administrative costs (pkr 85,730,725), and it comprises 3.92% of the total cost.